Globalisation effect on inflation in the great moderation era: New evidence from G10 countries - Duo Qin; Xinhua He (Kiel Institute for the World Economy (IfW), 2012)
Dynamic econometric models are carefully built to analyse counterfactually the globalisation effect on inflation for ten countries from G10 during the Great Moderation period. The main findings are (i) the effect is highly heterogeneous from country to country; (ii) increases in trade openness could be either inflationary or deflationary whereas increased imports from low-cost emerging-market economies are mostly deflationary; and (iii) there is almost no direct globalisation impact as far as inflation persistence is concerned while the impact on inflation variability can be positive as well as negative. Overall, globalisation is found to have contributed positively to lowering rather than stabilising inflation during the Great Moderation era.
Keywords: C52; E31; E37; F41; 330; inflation dynamics; globalisation